2014
DOI: 10.1002/hep.26738
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte cell-derived chemotaxin 2 antagonizes MET receptor activation to suppress hepatocellular carcinoma vascular invasion by protein tyrosine phosphatase 1B recruitment

Abstract: Leukocyte cell-derived chemotoxin 2 (LECT2) has been shown to act as a tumor suppressor in hepatocellular carcinoma (HCC). However, the underlying mechanism has not yet been completely defined. Here, we employ a LECT2-affinity column plus liquid chromatography coupled with tandem mass spectrometry to identify LECT2-binding proteins and found that MET receptor strongly interacted with LECT2 protein. Despite the presence of hepatocyte growth factor, the LECT2 binding causes an antagonistic effect to MET receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 28 publications
3
76
1
Order By: Relevance
“…Most recently, it was reported that LECT2 can bind to the receptor tyrosine kinase human c-mesenchymal epithelial transition factor (c-Met). This binding is antagonistic to the c-Met receptor activation, and LECT2 acts as a tumor suppressor in HCC (32). This finding suggests an alternative function in which LECT2 is involved in protein-protein interaction.…”
Section: Leukocyte Cell-derived Chemotaxin 2 (Lect2)mentioning
confidence: 92%
See 1 more Smart Citation
“…Most recently, it was reported that LECT2 can bind to the receptor tyrosine kinase human c-mesenchymal epithelial transition factor (c-Met). This binding is antagonistic to the c-Met receptor activation, and LECT2 acts as a tumor suppressor in HCC (32). This finding suggests an alternative function in which LECT2 is involved in protein-protein interaction.…”
Section: Leukocyte Cell-derived Chemotaxin 2 (Lect2)mentioning
confidence: 92%
“…The interaction between LECT2 and c-Met ECD has been demonstrated by coimmunoprecipitation experiments. The LECT2 binding caused an antagonistic effect on the c-Met receptor activation (32). In our study, the kinetic measurements of the interaction between these proteins were performed for the first time using surface plasmon resonance methods.…”
Section: Binding Of Lect2 To C-met Extracellular Domain (Ecd)-mentioning
confidence: 99%
“…A study on Ayu (plecoglossus altivelis) showed that LECT2 interacts with a C-type lectin receptor (32). Chen et al (33) recently showed that the inhibitory function of LECT2 on hepatocellular carcinoma is mediated by binding and inactivation of MET receptor, leading to blockage of vascular invasion and metastasis of hepatocellular carcinoma. Other studies showed that LECT2 negatively regulates the homeostasis of NKT cells in the liver (34,35).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…LECT2 protein was initially purified from a culture fluid of phytohemagglutinin-activated human T cell leukemia SKW-3 cells as a potential chemotactic factor for human neutrophils (24). Subsequent studies indicated that it is a multifactorial cytokine involved in chemotaxis, cell proliferation, immunomodulation, damage/repair process, tumor suppression, and glucose metabolism (33,36,(41)(42)(43)(44).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…LECT2 enhances macrophage function via the CD209a/DC-SIGN receptor and improves immunity in bacterial sepsis (53). More recently, it has been reported that LECT2 suppresses hepatocellular carcinoma by direct binding and inactivating hepatocyte growth factor (HGF) receptor MET (54). However, the role of LECT2 in the development of obesity and insulin resistance was unknown.…”
Section: Lect2mentioning
confidence: 99%